Smallholder Livelihood Diversification and Income Inequality in Rural Malawi - Takane, Tsutomu; Gono, Hiroko (Advances in Social Sciences Research Journal, 2017)
Prior literature on rural livelihood diversification in Africa has suggested it has tended to increase inequality. Drawing on household data collected in nine Malawian villages over a decade, this paper examines the interrelationship between livelihood diversification and income inequality. Analysis of income portfolio and Gini coefficients shows that the interrelationship is highly varied and, in many cases, livelihood diversification decreases inequality. The varied situations stem from different contexts, such as proximity to a major town, entry barriers to off-farm activities, and variability of own-farm income. The highly variable situations found in rural Malawi call for a more context-specific policy intervention, rather than a nationwide single prescription.